Independent risk factors for long-term skeletal relapse after mandibular advancement with bilateral sagittal split osteotomy. Issue 6 (June 2020) - Chen, Y.; Zhang, J.; Rao, N.; Han, Y.; Ferraro, N.; August, M.
Abstract: The purpose of this retrospective cohort study was to identify the independent risk factors for long-term skeletal relapse following mandibular advancement with bilateral sagittal split osteotomy. Univariate and multivariate linear regression analyses were performed including nine common risk factors for relapse as independent variables and horizontal/vertical long-term (≥2 years) skeletal relapse as dependent variables. Ninety-six patients were analyzed; 66 were female (68.8%) and the average age of the patients was 29.7 ± 10.5 years. Over an average follow-up of 3.8 ± 1.8 years after an initial mandibular advancement of 8.8 ± 2.4 mm, long-term skeletal relapse of 1.6 ± 1.0 mm horizontal and 0.9 ± 0.7 mm vertical was found. Multivariate analysis identified age, preoperative mandibular plane angle (MPA), bimaxillary surgery, counterclockwise mandibular rotation, and the magnitude of mandibular advancement to be significantly associated with horizontal long-term skeletal relapse. Preoperative MPA, counterclockwise mandibular rotation, and the magnitude of mandibular advancement were significantly associated with vertical long-term skeletal relapse. Thus preoperative MPA, the magnitude of mandibular advancement, and counterclockwise mandibular rotation of the mandible were found to be independent risk factors for both horizontal and vertical long-term skeletal relapse. Although long-term skeletal relapse cannot be avoided entirely, understanding the independent risk factors and their contributions will optimize treatment planning and long-term stability.